Idiopathic Carotidynia. (April 2017) - Policha, Aleksandra; Williams, David; Adelman, Mark; Veith, Frank; Cayne, Neal S.
Idiopathic carotidynia is a syndrome characterized by pain and tenderness over the carotid artery without an associated structural luminal abnormality. Controversy exists over whether this is a distinct disease entity or merely a symptom attributable to other causes of neck pain, such as carotid dissection or vasculitis. A 50-year-old woman presented with sudden-onset right neck pain. Imaging studies demonstrated transmural inflammation of the proximal internal carotid artery, without evidence of intraluminal pathology. The patient was placed on low-dose aspirin and ibuprofen. Her symptoms resolved within a week. At 3-month follow-up, her carotid artery appeared normal on duplex ultrasonography.